Chaotic Encryption-Based Network Robot for Indoor Security and Remote Video Monitoring - Zhang, Man; Chen, Ning (Informatica, 2024)
As society develops and living standards improve, people are putting forward higher and higher requirements for their living environment. In order to meet the needs of indoor security, fire security and building automation, intelligent robotics has come into being. Video data under intelligent network remote monitoring is different from traditional data, as video is a kind of data with a large amount of information, highly complex coding and decoding, difficult to process and requires real-time operation. Therefore, it is important to focus on the format characteristics of H.264 when designing the encryption scheme. Due to the heavy computational burden caused by the large amount of video data, it is not possible to encrypt all data when encrypting video data, and at the same time to ensure that the The traditional encryption algorithms, such as DES and RSA, are no longer suitable for video encryption applications in order to ensure that the format specificity and good operability are not compromised. Therefore, the aim of this paper is to design a sufficiently secure and practical video encryption scheme for remote monitoring of network robots based on the H.264 codec standard by introducing a chaotic iterative system, and finally to design and implement an indoor security method for remote monitoring of video technology based on chaotic encryption for network robots with certain practical application value.